PENGENDALIAN SOSIAL SISWA TIDAK MEROKOK (Studi di SMP Negeri 3 Sungai Raya Kabupaten Kubu Raya) - Maharani, Rini; Zakso, Amrazi; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the enforcement of social control of smoking student prevention at school. The focus of this research discusses the form of social control and efforts made to keep other students from smoking. This is a descriptive study at SMPN 3 Sungai Raya Kubu Raya Regency using a qualitative method with the form of descriptive analysis. Based on the findings, the preventive actions taken by the school to the students were by putting up prohibition signs on the walls and in written form in the school rules. For further preventions, the school provides socialization to students during the flag ceremony and education through collaboration with other agencies such as the National Narcotics Agency (BNN) and the Health Department (Dinkes). Based on the discussion, it was concluded that the social control of smoking student prevention conducted by SMPN 3 Sungai Raya Kubu Raya Regency had been well done.Â Â Keyword: Social Control, Smoking Student Prevention